Topics in Dynamics of Bridges, Volume 3 Proceedings of the 31st IMAC, A Conference on Structural Dynamics, 2013 - Cunha, Alvaro; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Topics in Dynamics of Bridges, Volume 3: Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the third volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Vibration Monitoring Damping Damage Detection Health Monitoring Dynamic Behavior Dynamic Modeling Human-Induced Vibration.
From the Contents: Vibration Analysis and Structural Identification of a Seismically Isolated Bridge -- Cable-Stayed Footbridge: Investigation Into Superstructure and Cable Dynamics -- Modal Parameter Identification of Bridges Under the Effect of Environmental Factors -- Analysis and Mitigation of Vibration of Steel Footbridge With Excessive Amplitudes -- Change in Mass and Damping on Vertically Vibrating Footbridges due to Pedestrians -- Predicting Footbridge Response Using Stochastic Load Models -- Temperature and Traffic Load Effects on Modal Frequency for a Permanently Monitored Bridge -- Structural Monitoring and Analysis of Bridges for Emergency Response -- Long-Term Modal Analysis of the New Carquinez Long-span Suspension Bridge -- Field Vibration Monitoring of a Cable-stayed Bridge Using Imote2-platformed Wireless Sensors.
Keywords: Civil engineering; Vibration; Dynamical systems; Dynamics; Mechanics; Mechanics, Applied; Civil Engineering; Vibration, Dynamical Systems, Control; Solid Mechanics